Malaysian and Indonesian Learners: They are Judges of How They Learn English Most Effectively in and out of Classrooms - Nur Huslinda Dato’ Che Mat; Laila Ulsi Qodriani; M. Yuseano Kardiansyah (TEKNOSASTIK, 2016)
The position of English is that of a Second Language in Malaysia and a Foreign Language in Indonesia. But the objective is the same that is to enable the learners to communicate effectively and efficiently in social and professional situations.  Learners’ beliefs and learners’ strategies are also part of the learning processes. Strategies are ways of managing the complex information that the learners are receiving about the target language. This study aims to find out (i) the learners’ beliefs on the importance of English (ii) what the learners will do (strategies) to manage their own learning. 100 respondents participated in the study. They responded to open ended questions. The results show that there are similarities and differences in the ways the Malaysian and Indonesian learners perceived the importance of English. They also have similarities and differences in their strategies to manage their own learning to achieve their goals.  As a conclusion, even though the two countries adopted different language policy, the learners of English as a Second and Foreign Language have their own enthusiasms and they make judgements about how to learn the language effectively and they have the awareness of what language learning is like.